Fifty shades of an inhabited woman: Qualitative study of the Fifty Shades of Grey trilogy - Linares Bahillo, Estibaliz (Papers. Revista de Sociologia, 2016)
This qualitative research study analyses the Fifty Shades of Grey trilogy from a gender perspective and feminist reading. Additionally, it attempts to understand the keys to the trilogy’s success through the discourse of female readers. To achieve this aim, the research is divided into two phases. Using the content analysis method, the first phase focuses on identifying and analyzing the myth of romantic love, stereotypical social structures, and gender stereotypes in terms of sexual relationships within the novel. Based on the results of the analysis, two women’s discussion groups are formed in the second phase; each comprising 6 women aged between 16-22 and 40-50 years old who have read this bestselling trilogy. The aim of the discussion groups is to understand the motivations and opinions of these women regarding their reading of the trilogy and identify gender stereotypes.